2018
DOI: 10.1002/jclp.22696
|View full text |Cite
|
Sign up to set email alerts
|

Exercise dependence: Associations with capability for suicide and past suicidal behavior

Abstract: Objective Exercise dependence has been linked to capability for suicide and suicidal behavior; however, less understood are which facets of exercise dependence confer risk for suicidal behavior and the potential mechanisms of this association. This study examined relationships between exercise dependence, capability for suicide, and past suicidal behavior. Methods A sample of 540 individuals recruited via MTurk completed online measures of their exercise dependence, capability for suicide, and history of suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Suicide attempts, however, were measured inconsistently. Most studies ( n = 21) asked the participant one question about whether they had attempted suicide with questions differing in linguistic structure (see [ 56 , 57 ]). Ten studies assessed participant suicide attempt using an interview conducted by a psychiatrist/medical professional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide attempts, however, were measured inconsistently. Most studies ( n = 21) asked the participant one question about whether they had attempted suicide with questions differing in linguistic structure (see [ 56 , 57 ]). Ten studies assessed participant suicide attempt using an interview conducted by a psychiatrist/medical professional.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies that investigated potential relationships between painful and provocative events and acquired capability, more than half ( n = 8) were published in the past five years with 11 studies reporting significant relationships. Events include generally experiencing more painful and provocative events [ 60 ], traumatic experiences including NSSI [ 98 ], continuing to exercise despite pain and exhaustion [ 57 , 63 ], substance use [ 99 ] and childhood abuse [ 85 ]. Studies looking at perpetrators of violence found perpetrators had an increased acquired capability [ 100 ] compared to victims of violence [ 94 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…The items within the functional impairment subscale include feeling depressed or anxious when missing exercise sessions and canceling social activities because of needing to exercise. Past work has found this type of dependence on exercise is associated with negative outcomes (Rogers et al, 2019; Unger, 1997), including suicide attempts. One possible explanation for this counterintuitive finding is that individuals who attempted suicide have since received treatment, leading them to currently endorse lower functional impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Lower subjective well-being has been identified as one of the important factors contributing to high suicide rates, loneliness, and depression in older people ( Wu et al, 2014 ; Bartlett and Arpin, 2019 ; Soósová et al, 2021 ). Physical exercise, as an external aid known to effectively counteract negative human emotions, will help to reduce the risk of suicide and depression, as well as loneliness ( Sun and Stuart, 2002 ; Chen et al, 2010 ; Rogers et al, 2019 ). This can increase one’s subjective well-being.…”
Section: Discussionmentioning
confidence: 99%